Apparent Reasons and Practical Steps of Aāmm-ūr-Remādah in the light of Uswa’-e-Fārūqī - Abdul Ghaffar; Qasim, Tanveer; Ahmad, Hafiz Intizar (Journal of Islamic and Religious Studies, 2020)
Haḍrat ‘Umar (R.A) had great insight and comprehension in reliving all political, religious, social, and judicial issues, in the light of Islam. He solved every individual and collective issue immediately without imposing his opinion on others but presented his views with communication and understanding. He faced criticism against his opinion and did not impose his jurisprudence without understanding. This system was continued during his whole period of regency. This symmetry of his character had given him great value among ummāh. According to shah wāliullah, he had all qualities of Sharī’ah in his thoughts and practice. The administration and jurisprudence of Ḥaḍrat ‘Umar (R.A) are just like prim for Ummah, which exposes to light in a different spectrum. We can solve while the contemporary problem in the light of Ḥaḍrat ‘Umar’s (R.A) administrative system. This paper intends to find out the methods he used to control epidemics, famine, and malnutrition and concludes that by adopting his methods we can get rid of all political, religious, social, and judicial issues especially the epidemic of COVID 19.